Flow reduction of a high‐flow arteriovenous fistula in a hemodialysis patient reveals changes in natriuretic and renin–angiotensin system hormones of relevance for kidney function. Issue 19 (4th October 2021) - Meyer‐Olesen, Christine L.; Lindhard, Kristine; Jørgensen, Niklas R.; Goetze, Jens P.; Bomholt, Tobias; Jensen, Boye L.; Hansen, Ditte
Abstract: Arteriovenous fistulas (AVFs) are iatrogenic vascular connections established to allow high‐flow intravascular access for patients with chronic kidney disease requiring hemodialysis. The left‐right flow shunt results in changes in extracellular fluid volume and blood pressure‐controlling hormones that could affect the residual kidney function. We present a case where a female patient with a brachiocephalic AVF had a fistula flow of >4 L/min. To reduce the flow, a banding procedure was performed. The patient was examined prior to banding and 1 and 2 weeks thereafter. Banding resulted in a marked decrease in AVF flow from >4 to 1 L/min and was associated with reductions in N‐terminal pro‐brain natriuretic peptide of 51% and 67% at 1‐ and 2‐weeks post‐banding, respectively. Mid‐regional pro‐atrial natriuretic peptide concentrations were reduced post‐banding by 17% after 1 week and 25% after 2 weeks. After 1 week, renin, angiotensin II, and aldosterone levels in plasma decreased transiently by 44%, 47%, and >86%, respectively, and returned to pre‐banding levels after 2 weeks. Creatinine clearance tended to decrease while blood pressure and total body water increased 2 weeks after banding. This indicates that high‐flow AVF is associated with increased natriuretic peptides and hormones of the renin–angiotensin–aldosterone system, that may balance each other regarding fluid retention and hypertension and support remaining kidney function. Abstract : A patient with end‐stage kidney disease and an arteriovenous fistula with extreme access flow of >4 L/min underwent flow reduction to 1 L/min by banding. Flow reduction was associated with increased total body water and blood pressure and reduction in natriuretic peptide hormones along with temporary decreased hormones of the renin—angiotensin—aldosterone system and a small decrease in creatinine clearance. This indicates that a high‐flow arteriovenous fistula is associated with hormonal changes that may balance each other regarding fluid retention and hypertension and support remaining kidney function.